Effect of Service Quality on Satisfaction and its Impact on Loyalty of Santri Pesantren Student Al Ma'soem - Dadang Dimyati (UIN Sunan Gunung Djati Bandung, 2017)
This study aimed to analyze the influence of service quality on satisfaction and the impacts on loyalty intention of students Al Ma’soem Boarding School. The research data was obtained from primary data by distributing questionnaires to 100 students of junior high school and senior high school in Al Ma’soem Boarding School. The findings of this study indicate that there is influence between the Service quality and satisfaction on the loyalty students in Al Ma’soem Boarding School. F test results showed that the Service quality and the satisfaction simultaneously affect to loyalty students in Al Ma’soem Boarding School. The R-square value obtained amounted to 0.417, or 41,7%, meaning that simultaneous Service quality and satisfaction contribute to the effect of 41,7% on loyalty students in Al Ma’soem Boarding School, as for the influence of others factors are 58,3%.